Nutrition in acute pancreatitis: a critical review. (3rd May 2016) - Lodewijkx, Piet J; Besselink, Marc G; Witteman, Ben J; Schepers, Nicolien J; Gooszen, Hein G; van Santvoort, Hjalmar C; Bakker, Olaf J; on behalf of the Dutch Pancreatitis Study Group,
ABSTRACT: Severe acute pancreatitis poses unique nutritional challenges. The optimal nutritional support in patients with severe acute pancreatitis has been a subject of debate for decades. This review provides a critical review of the available literature. According to current literature, enteral nutrition is superior to parenteral nutrition, although several limitations should be taken into account. The optimal route of enteral nutrition remains unclear, but normal or nasogastric tube feeding seems safe when tolerated. In patients with predicted severe acute pancreatitis an on-demand feeding strategy is advised and when patients do not tolerate an oral diet after 72 hours, enteral nutrition can be started. The use of supplements, both parenteral as enteral, are not recommended. Optimal nutritional support in severe cases often requires a tailor-made approach with day-to-day evaluation of its effectiveness.